Proprioceptive Training in the Prevention of Ankle Sprain in Athletes: A Narrative Review - I Kadek Angga Raditya; Made Ngurah Kresnadana Putra Utama; Ni Made Risma Mutia Maharani; I Made Egga Adika Suputra; I Made Handyka Peramas Dharmasunu (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Ankle sprain is one of the most common musculoskeletal injuries among athletes, characterized by high prevalence and significant impacts on performance, quality of life, and a high risk of recurrence leading to chronic ankle instability (CAI). Objective: To review current scientific evidence on the effectiveness of proprioceptive training as a primary and secondary prevention strategy for ankle sprains in the athletic population. Methodology: This narrative literature review was conducted by searching PubMed, Scopus, and Google Scholar databases using the keywords proprioceptive training, ankle sprain prevention, athletes, balance exercise, and injury prevention. Selected articles included relevant intervention studies, cohort studies, and systematic reviews. Results: Scientific evidence consistently demonstrates that proprioceptive training significantly reduces the incidence of ankle sprain by up to 38%. Its mechanism involves enhancing neuromuscular control, improving joint position sense (JPS), and optimizing protective reflexes through neuroplastic adaptations at both peripheral and central levels. Proprioceptive training offers superior long-term functional adaptations. Discussion: Impaired neuromuscular control resulting from proprioceptive deficits is the root cause of the high recurrence rate of ankle sprains. Proprioceptive training directly targets this mechanism, making it a more fundamental intervention than bracing, which only provides external mechanical stability, or strengthening, which does not fully address coordination deficits. The combination of proprioceptive training and strengthening yields the most comprehensive results. Conclusion: Proprioceptive training is an essential, evidence-based intervention in ankle sprain prevention and rehabilitation programs for athletes. This approach is effective in restoring sensorimotor function, enhancing joint stability, and significantly reducing the risk of recurrent injury. Recommendation: The implementation of proprioceptive training should become a standard in injury prevention protocols for athletes. Future research is recommended to focus on optimizing the dose, frequency, and progression of exercises, as well as utilizing neurophysiological biomarkers to map neural adaptations.